Analisis Permintaan Karet Alam Indonesia di Pasar Internasional - Happy Dewi Purnomowati; Dwidjono Hadi Darwanto; Sri Widodo; Slamet Hartono (Universitas Muhammadiyah Yogyakarta, 2015)
The development of the natural rubber market in three years was relatively favorable for producers, which was indicated by the relatively high price level. This was due to increasing demand. Of course this will be a good opportunity for Indonesia to export processed rubber and rubber industry in Indonesia to other countries. The purpose of this study was to determine the factors that can affect demand for Indonesia's natural rubber exports in each country's export destinations. The data used was secondary data years 1980-2013 time series derived from IRSG, BPS, FAO, Gapkindo, UN Comtrade, BI, and the World Bank. Methods of analysis using dynamic demand model